Celebrating 50 Years as the Trusted Source for Agricultural Science and Technology - Chimenti, Linda M. (Council for Agricultural Science and Technology (CAST), 2021)
The Council for Agricultural Science and Technology (CAST) is celebrating 50 years as the trusted source for credible, balanced, science-based information in 2022. This commemorative publication offers three sections covering 1) CAST historical highlights, publications, social media, and organizational structure, 2) the impact of CAST, and 3) essays on the future of CAST.CAST is planning a year-long celebration of this important milestone. A number of meetings and presentations will take place to share this publication and engage stakeholders to get their ideas, input and suggestions about how CAST adapts to new challenges to science communications around food, agriculture, and the environment. These events will culminate at the 2022 CAST Annual Meeting which will be held in Iowa, where CAST was formed and still currently operates.
Keywords: Celebration; CAST; History